Diagnostic and prognostic significance of lysophosphatidic acid in malignant pleural effusions - Bai, Cui-Qing; Yao, Yan-Wen; Liu, Chun-Hua; Zhang, He; Xu, Xiao-Bing; Zeng, Jun-Li; Liang, Wen-Jun; Yang, Wen; Song, Yong (Journal of Thoracic Disease, 2014)
Background: Lysophosphatidic acid (LPA) is an important extracellular signal transmitter and intracellular second messenger in body fluids. It can be detected in the ascitic fluid of patients with ovarian cancer. Increasing evidence shows that LPA can stimulate cancer cell proliferation and promote tumor invasion and metastasis. Our study aimed to evaluate the diagnostic value of LPA in differentiating between malignant pleural effusions (MPEs) and benign pleural effusions (BPEs) and to evaluate the association between the level of LPA in MPE and the prognosis of lung cancer patients. Patients and methods: The level of LPA in the pleural effusions (PEs) of 123 patients (94 MPE, 29 BPE) with lung cancer was evaluated using an enzyme-linked immunosorbent assay. The performance of LPA was analyzed by standard Receiver operator characteristic curve (ROC) analysis methods, using the area under the curve (AUC) as a measure of accuracy. Overall survival (OS) curves and progression-free survival (PFS) curves were based on the Kaplan-Meier method, and the survival differences between subgroups were analyzed using the log-rank or Breslow test (SPSS software). A multivariate Cox proportional hazards model was used to assess whether LPA independently predicted lung cancer survival. Results: The levels of LPA differed significantly between MPE (22.08±8.72 μg/L) and BPE (14.61±5.12 μg/L) (P